Angiographic Pattern of Arterial Stenosis Among Different Subtypes of Cerebral Infarct (Bangladesh Journal of Neuroscience, 2026)
Background: Ischemic stroke can be caused by atherosclerotic occlusion, cardioembolism, occlusion of small vessels or hypoperfusion. These may lead to different types of infarcts like territorial, sub-cortical, lacunar or water-shed infarct. There are little data regarding the degree of stenosis of cerebral arteries and different subtypes of cerebral infarct.Objective: The objective of this study was to find out the angiographic pattern of arterial stenosis among different subtypes of ischemic stroke patients.Materials and Methods: We evaluated 93 ischemic stroke patients from indoor, outdoor, stroke and neuro intervention clinic, BSMMU. CT scan and/ or MRI of brain were done to each patient to confirm the diagnosis. After vascular imaging, the degree of stenosis was measured by the NASCET formula.Results: Total 93 ischemic stroke patients with significant symptomatic stenosis were studied. Analysis of age distribution showed that mean age was 57.4±1.01 years with range 35-79 years with male female ratio of 1.51:1. Among them 45(48.4%) had extra-cranial stenosis, 42(45.2%) had intra-cranial and 6(6.4%) had both extra-cranial and intra-cranial stenosis. Territorial infarct was seen in 40(43.0%) patients, subcortical infarct in 21(22.6%) patients, lacunar infarct in 26(28.0%) patients and water-shed infarct in 6(6.4%) patients. There was significant association of subtype of infarct with location of stenosis (p-value=0.50). We also observed significant association of subtype of infarct with degree of stenosis (p-value